Participation in crop maximization project, empowerment and well-being among small farmers of Sindh Province, Pakistan - Mujtaba, Khushk Ghulam (2017)
The ultimate aim of community development is to improve the quality of life and well-being of community members. Achieving the well-being of community members through participation and empowerment approach is claimed to be effective in developing countries. These approaches of community development aim to engage or involve members of the community inthe process of improving their life conditions. It is also used as a strategy by government at the local level to provide a platform to improve the standard of living and quality of life of the people. Like other developing countries, the government of Pakistan through its agricultural department launched various development projects/ programs (i.e. Micro-finance schemes, food security programs, poverty alleviation program, farmers’ field school, crop-maximization projects, etc.) in order to improve the standard of living and quality of life of small farmers communities. In line with this, the present study focused on establishing the relationship between participation, empowerment and well-being among small farmers who participated in crop maximization project. This quantitative study surveyed 455 small farmers from six districts of the Sindh province of Pakistan who participated in crop maximization project using multistage cluster sampling technique. The result of this study showed that the socio-economic conditions of small farmers of the Sindh who participated in crop maximization project were low. The study revealed that, the level of participation was high but both empowerment and well-being were moderate. Further, the analysis of structural equation model indicated that the standardized path coefficient were consistent with the hypothesized model by indicating a large effect sizes which means that, participation contributes significantly to empowerment (β = .546, p < .05) and well-being (β = .585, p < .05). The first layer of analysis indicated that participation was statistically significant and positively related to empowerment (p < .05) and well-being (p < .05). In addition, the analysis of structural equation model indicated that the standardized indirect path coefficients of empowerment was significant to participation (p < .05) and well-being (p < .05) which indicated that, empowerment was a mediator in the relationship between participation and well-being. Based on the results, the researcher concluded that, there is a significant relationship between participation, empowerment and well-being; and empowerment also leads to the well-being of the small farmers of the Sindh province in Pakistan. This study also supported the theories that established a link between participation, empowerment and well-being. Findings of this study can be used by the Sindh/Pakistan government, agricultural department of the Sindh, Pakistan, non-governmental organizations (NGOs) and policy makers to develop their policies and strategies for the betterment of the peasant communities in future.